The Trends of Neonatal Mortality Rate Among South East Asia Countries from 2000-2017 - Soleman, Sani Rachman (Disease Prevention and Public Health Journal, 2020)
Background: Neonatal MortalityRate (NMR) reflects the quality of health services provided by the government. It is very important to disclose the health system capability of each country in managing mother and child health programs because it is an essential health policy that should be prioritized.  The health system capability of a country will determine the welfare and social guarantee because most of NMR causes are preventable. Several components such as maternal factors, neonatal and health services were determined as predictors of NMR. The objective of this study is to compare neonatal mortality trends among eight South East Asia Countries (SEAC) from 2000 to 2017. Method: A cross-sectional design was used to analyze the data regarding the causes of neonatal death between 2000 and 2017. Data were taken from World Health Organization Maternal Child Epidemiology Estimation (WHO MCEE) database.The collected data were live birth; neonatal mortality rate; and the big five of neonatal mortality etiologies in the eight SEAC.  Data were then analyzed descriptively with line chart to describe the trend of NMR. Result: This study found that Indonesia  had the highest neonatal mortality rate, yet the trend decreased gradually from 102.700 in 2000 to 60.986 in 2017, followed by Philippines, Vietnam, Myanmar, Cambodia, Thailand, Laos, and Malaysia respectively.  On the other hand, the trend of live birth was the lowest in Indonesia  and the highest in Philippines . According to the data regarding the leading cause of NMR, preterm birth was the major cause of neonatal mortality followed by birth asphyxia and congenital defects. Conclusion: Indonesia has the highest mortality rate, yet the etiology such as as premature birth, asphyxia, and congenital disorder is similar to the other eight countries.